(untitled) - Vojtekova, Maria; Blazekova, Olga (Doprava a spoje, 2012)
Transportation problem is one of the basic linear programming problems and it has a place in the Operation research course. Transportation problem can be solved by simplex method and there are special methods too: NW corner method, index method, Vogel's approximation method, … The aim of our paper is to show using of lesser-known Russel's approximation method and its comparison with used Vogel's approximation method.